Comparative Analyses of Lycodon rufozonatus and Lycodon rosozonatus Gut Microbiota in Different Regions - Fei Zhu; Ke Sun; He Zhang; Jing Lu; Peng Guo; Jiaqi Zhang; Yu Xu; Bing Lyu (Ecology and Evolution)
ABSTRACT The interactions between hosts and the gut microbiota are intricate and can significantly affect the ecology and evolution of both parties. Various host traits, including taxonomy, diet, social behaviour, and external factors such as prey availability and the local environment, all play an important role in shaping composition and diversity of the gut microbiogta. In this study, we explored the impact of intestinal microorganisms on the host in adapting to their respective ecological niches in two species of snakes. We collected feces from Lycodon rufozonatus and Lycodon rosozonatus from different geographical locations and used 16S rRNA gene sequencing technology to sequence the v3‐v4 region. The results revealed that there was no significant difference in the alpha diversity of intestinal microorganisms between L. rufozonatus and L. rosozonatus. The gut microbiota of all individuals comprised four main phyla: Pseudomonadota, Bacteroidota, Bacillota, and Actinomycetota. At the genus level, the genus Salmonella dominated the enterobacterial microbiota in the samples from Hainan, while there was no obvious dominant genus in the enterobacterial microbiota of the samples from the other four localities. Comparative analysis of enzyme families annotated to the gut microbiota between L. rufozonatus and L. rosozonatus from the four sampling regions by CAZy carbohydrate annotation revealed that nine enzyme families differed significantly in terms of glycoside hydrolases (GHs). In addition, we compared the composition of gut microbial communities between L. rufozonatus and L. rosozonatus and investigated the impact of the differences on their functions. Our results will provide insights into the coevolution of host and gut microbes.